Public Infrastructure Problem For Developing Tourism Destinations In Coastal And Small Islands Areas Case Study In Karimunjawa Archipelago - Jamilla Kautsary (International Conference on Coastal and Delta Areas, 2017)
Karimunjawa is one of the archipelago in the north of Java island. It has uniqueness of nature. In these archipelago, five forms of ecosystems can be found. One of the exciting ecosystems and the main attraction of tourists who come to Karimunjawa is Coral Reef. The number of tourists who visit to Karimunjawa is increase along with the ease of transportation and the many choices of modes to Karimun although in the west monson This condition would bring both positive and negative impacts. The increase number of tourists who visit to Karimunjawa has not been followed by the readiness to provide adequate infrastructure.It is causing the emergence of various problems in Karimunjawa. The aims of this study is to reveal the problems of public infrastructure in developing tourist destinations in coastal areas and small islands. This research uses rationalistic deductive method, with empirical description analysis technique. The findings obtained from this research are the emergence of environmental issues such as water supply, electricity and telecommunication and waste management problems. Keywords: public infrastructure, tourism , Karimunjawa